THE ANALYSIS OF FACTORS THAT AFFECT THE COST OF THE SOIL WORK OF THE ROAD PROJECT - Riza Fandopa, Sofia W. Alisjahbana, Dadang M. Ma’soem (International Journal of Advanced Science and Technology, 2020)
Road infrastructure in Indonesia allows the movement of 70% of goods and 30% of passengers from outside the city. Roads are the most important access for both economic and development activities. Currently, the construction of roads is carried out in almost all regions of Indonesia. The government targeted 2,650 kilometers (km) of road construction with a total budget of Rp.733 trillion [1], in the 2015-2019 National Medium-Term Development Plan (RPJMN). In the implementation, the landfill work is a dominant part of the project. The accuracy in estimating the cost of the borrowed land is necessary as it greatly affects the overall performance of the project cost. The purpose of this research is to design the estimated unit cost of the borrowed land and to identify several factors that influence it. The study was carried out on 20 projects in Java and Sumatra. The method that is used is multiple linear regression by using SPSS software. The estimated models are: Y = 29,718 + 1,621 (X1) + 0,111 (X2) + 2,479 (X4) - 0.578 (X5) + 2,514 (X6) - 0.048 (X7) - 0.538 (X8). Where Y = Cost of the borrowed landfill work (Rupiah/M3), X1 = Loose soil price (Rupiah/M3), X2 = Loose soil usage, X4 = Diesel price (Rupiah/Liter), X5 = Transport capacity (Ton), X6 = Loose soil hauling distance (Km), X7 = Effective working hours (Hours/month), X8 = Production capacity (M3/Hour).